علاقة تفويض السلطة بالأداء الوظيفي لدى العاملين "دراسة ميدانية على عينة من العمال الإداريين لبلدية حاسي خليفة - دلال فطحيزة على; الأطرش نبيلة (جامعة الوادي - University of Eloued, 2025)
" نظرا لأهمية موضوع تفويض السلطة في عملية تحسين الأداء الوظيفي ,أصبح ا من بين أنجع الإستراتجيات المستخدمة في المؤسسات للوصول للأهداف المنشودة للمنظمة . حيث تناولنا في هذه المذكرة موضوع ""علاقة تفويض السلطة بالأداء الوظيفي لدى العاملين""، من خلال دراسة ميدانية على عينة من الموظفين الإداريين ببلدية حاسي خليفة، إحدى بلديات ولاية الوادي. وتأتي أهمية الموضوع من كونه يركز على تفويض السلطة كاستراتيجية تنظيمية حديثة وفعالة لتحسين جودة الأداء وزيادة فعالية المؤسسات، خاصة في إطار الجماعات المحلية. تمحورت الدراسة حول إشكالية أساسية هي: إلى أي مدى يساهم تفويض السلطة في تحسين الأداء الوظيفي لدى موظفي بلدية حاسي خليفة؟ وانبثقت عن هذه الإشكالية مجموعة من الأسئلة الفرعية المتعلقة بمستوى التفويض، وطبيعته، وانعكاساته على سلوك الموظفين، ومدى إسهامه في تدريبهم وتحفيزهم. اعتمدت الدراسة على المنهج الوصفي التحليلي كإطار منهجي، واستخدمت أداة الاستبيان لجمع البيانات من عينة قصدية مكونة من 60 موظفًا إداريًا، من أصل 148 يمثلون مجتمع البحث. كما تم تحليل المعطيات باستخدام النسب المئوية والجداول التكرارية والدوائر النسبية. حيث أظهرت النتائج أن هناك علاقة إيجابية بين تفويض السلطة وتحسين الأداء الوظيفي، حيث أكد غالبية الموظفين أن الصلاحيات المفوضة تساعدهم في أداء مهامهم بشكل أكثر فعالية، وفي اتخاذ القرار، وتشخيص المواقف، وجمع المعلومات، كما تساهم في تنمية الثقة بالنفس والاعتماد على الذات وتحفيز روح الانتماء. تم تفسير هذه النتائج ضمن إطارين نظريين: نظرية فليب سلزنيك التي ترى أن التفويض يسهم في دمج الأنساق الفرعية في التنظيم ويعزز الضبط الداخلي؛ ونظرية التحليل الاستراتيجي لميشال كروزيه التي توضح أن التفويض يمنح الفاعلين حرية نسبية في التفاعل التنظيمي، مما يحسن الأداء ويزيد الفعالية. توصلنا من خلال هذه لدراسة لجملة من التوصيات ، أبرزها ضرورة إرساء ثقافة التفويض داخل المؤسسات المحلية، وتكوين الموظفين في مهارات التسيير وتحمل المسؤولية، وتطوير سياسات إدارية تدمج بين الرسمي وغير الرسمي بما يحقق الانسجام والمرونة. وبالتالي، فقد أبرزت هذه الدراسة الدور الفعال لتفويض السلطة في تحسين الأداء الوظيفي، وأكدت على أهميته كأداة من أدوات الحوكمة الإدارية في المؤسسات العمومي ""The importance of the concept of delegation of authority in enhancing job performance, it has become one of the most effective strategies employed by organizations to achieve their desired objectives. This study addresses the topic ""The Relationship Between Delegation of Authority and Job Performance Among Employees"" through a field investigation conducted on a sample of administrative staff at the Municipality of Hassi Khalifa, one of the municipalities of El Oued Province. The significance of the study stems from its focus on delegation as a modern and effective organizational strategy aimed at improving performance quality and increasing institutional effectiveness, particularly within the framework of local government. The central research question revolves around: To what extent does the delegation of authority contribute to enhancing job performance among employees of the Municipality of Hassi Khalifa? From this main question, several sub-questions were derived, concerning the level and nature of delegation, its impact on employee behavior, and its role in training and motivating staff. The study employed a descriptive-analytical approach as its methodological framework and utilized a questionnaire as the primary data collection tool, targeting a purposive sample of 60 administrative employees out of a total population of 148. Data were analyzed using percentages, frequency tables, and pie charts. The findings revealed a positive relationship between delegation of authority and improved job performance. The majority of participants confirmed that delegated powers aid them in performing tasks more effectively, making decisions, diagnosing situations, and gathering information. Additionally, delegation was found to enhance self-confidence, autonomy, and a sense of belonging. These result were interpreted within two theoretical frameworks: Philip Selznick’s theory, which suggests that delegation contributes to integrating sub-systems within an organization and reinforces internal control. Michel Crozier’s strategic analysis theory, which posits that delegation provides actors with relative freedom in organizational interaction, thereby improving performance and increasing effectiveness. Based on the study’s results, several recommendations were proposed, most notably: The necessity of establishing a culture of delegation within Training employees in management and responsibility-taking skills, and Developing administrative policies that integrate formal and informal elements to ensure harmony and flexibility. In conclusion, this study highlighted the effective role of delegation of authority in enhancing job performance and emphasized its importance as a key tool of administrative governance in public institutions. "
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع تنظيم وعمل
Keywords: العمال الإداريين; السلطة بالأداء; علاقة التفويض; The relationship between delegation; authority; performance; and administrative workers.